PERAN PEKSOS DALAM TARAUMA HEALING PADA KORBAN BENCANA TSUNAMI DI TANJUNG LESUNG BANTEN - Fuad, Syahrul Fadillah; Zulaikha, Siti; Fuad, Syahrul; Fitri, Yaumil (Social Welfare Study Program, 2021)
Abstract. The purpose of this activity is to provide psychological assistance and support to Tsunami victims in TanjungLesung, Banten. The method used for the victims of the Tsunami disaster is using trauma healing in the event, namely